2014
DOI: 10.3892/ijo.2014.2547
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of CXCR7 gene represses growth and invasion and induces apoptosis in colorectal cancer through ERK and β-arrestin pathways

Abstract: The CXC chemokine receptor 7 (CXCR7) has been reported to be involved in cell growth, metastasis and apoptosis in certain cancers. However, the function and molecular mechanisms of CXCR7 in human colorectal cancer (CRC) are still undefined. In the present study, sixty-eight cases of CRC tissues and corresponding adjacent non-cancer tissues (ANCT) were collected, and the expression of CXCR7 was assessed using immunohistochemistry (IHC) in biopsy samples. Furthermore, CXCR7 gene was silenced by small hairpin RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Numerous studies have shown that chemokines and their receptors are expressed in cancer and affect its development . Recently, it has been reported that CXCR7 is overexpressed in many types of cancer (eg, ovarian, colorectal, and breast) . Studies have shown that CXCR7—a G protein‐coupled receptor—has attracted attention due to its increased expression in colorectal cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that chemokines and their receptors are expressed in cancer and affect its development . Recently, it has been reported that CXCR7 is overexpressed in many types of cancer (eg, ovarian, colorectal, and breast) . Studies have shown that CXCR7—a G protein‐coupled receptor—has attracted attention due to its increased expression in colorectal cancer .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Recently, it has been reported that CXCR7 is overexpressed in many types of cancer (eg, ovarian, colorectal, and breast). [25][26][27] Studies have shown that CXCR7-a G protein-coupled receptor-has attracted attention due to its F I G U R E 5 ELISA: Expression of CXCR7 regulates VEGF secretion Notes: A, The levels of VEGF were significantly increased in SW480 and Caco-2 cells overexpressing CXCR7. Treatment with inhibitors LY294002 and U0126 reduced the levels of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR7, as a recently discovered chemokine receptor, has demonstrated its characteristics in six aspects out of the ten top hallmarks of tumors, including resisting cell death, inducing angiogenesis, sustaining proliferative signaling, activating invasion and metastasis, tumor-promoting inflammation, and cancer-related genes [14,[17][18][19][20][21][22]. Both CXCR4 and CXCR7 are receptors of chemokine CXCL12 and have been reported in multiple tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…There are literatures indicating that CXCR7 binds to CXCL12 with greater affinity than CXCR4 to CXCL12 (Kd = 0.4 nM versus 3.6 nM) [10,11]. Furthermore, the roles of CXCR7 in neovascularization, tumor invasion and proliferation have been verified [12][13][14]. On the other hand, the clinical pattern of CXCR7 in various cancers has not been thoroughly summarized, and controversy still exists in different researches.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, silencing of CXCR7 was shown to induce apoptosis in a β -arrestin- and ERK-dependent fashion. 13 However, whether β -arrestin and ERK pathway are involved in TFF3-dependent regulation of apoptosis in colon cancer progression and metastasis has still to be addressed.…”
mentioning
confidence: 99%